Campaña para incentivar el consumo de huevo en madres embarazadas de la provincia de Chimborazo. Caso: Ministerio de Inclusión Económica y Social - Borja Domínguez, Verónica María (2019)
Public health was created due to the spread of several diseases such as cholera. The United Kingdom was the first to take action on the matter and created laws around it. Currently, many of the methods used at the time are used worldwide. In Ecuador, the subject of public health came a little late. It is important to emphasize that there have not been many advertising campaigns for the benefit of society in Ecuador. For this reason it is important to take a step and be able to help those who most need a contribution through advertising and in this case also social marketing. Bearing in mind that the research focused on the importance of egg consumption in pregnant mothers in the province of Chimborazo, a province that has very high levels of illiteracy and malnutrition. The research was carried out in the province of Chimborazo, where research tools such as surveys were used to study consumer behavior, which in this case would be mothers and interviews to find out what experts say about it. Keep in mind that a social marketing campaign will not solve all the problems found in the province of Chimborazo, but it can be the first step to change a habit that will take several years. By carrying out the campaign seeks to educate pregnant mothers in the province of Chimborazo to bring better nutrition and their babies can be developed in a better way, to have a better future.